Implementasi Teknik Attahaddus 'Anil A'mal Al-Yaumiyah untuk Meningkatkan Keterampilan Berbicara Siswa Kelas 8 - Anjelhi, Anjelhi; Putra, Alfan; Takwim, Mardi (South Sulawesi Education Development, 2025)
The objectives of this study are (1) to determine how the application of the technique of talking about daily activities improves the speaking skills of eighth-grade students at Al-Hafidz Integrated Islamic Junior High School, Palopo, and (2) to find out whether the application of the technique of talking about daily activities can improve the speaking skills of eighth-grade students at Al-Hafidz Integrated Islamic Junior High School, Palopo. This type of research is classroom action research. The data collection methods used are observation and tests. The results of this study are (1) through the classroom action research conducted by the researcher, it can be concluded that the application of the technique of talking about daily activities can enhance the mastery and outcomes of speaking skills among eighth-grade students at Al-Hafidz Integrated Islamic Junior High School, Palopo, and (2) the level of improvement in the first cycle shows that out of 12 students, 10 students achieved a percentage of (83%), while the students who did not reach the percentage were (17%). Meanwhile, in the second cycle, all eighth-grade students achieved a percentage of (100%). From the first to the second cycle, there was a 17% improvement in learning outcomes. Thus, in the second cycle, the learning outcomes were fully achieved.